2019
DOI: 10.1063/1.5120459
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on the onset of elastic turbulence in swirling flow and curvilinear microchannels

Abstract: Elastic turbulence, which is sensitive with geometry and polymer itself, is capable of leading to improved performance of mixing, hear transfer and even oil recovery. Recently, the rheological properties of polymer solutions showed significant effects on the onset of elastic turbulence or instability. However, the variations of rheological properties based on polymer sensitivities such as salinity and its corresponding effects on the elastic turbulence have not been investigated. This work investigates systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…Our results are in agreement with studies showing an increased degree of elastic effects with reduced salt 40,49 and polymer concentrations. 28 Interestingly, Gulati et al observed no vortex formation at 40 μg mL −1 λ DNA but increasing vortex formation with higher Wi (corresponding to the Deborah number used in our work) for 400 μg mL −1 λ DNA, similar to the lack of waves for our 50 μg mL −1 sample but waves occurring at C ≥ 100 μg mL −1 .…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with studies showing an increased degree of elastic effects with reduced salt 40,49 and polymer concentrations. 28 Interestingly, Gulati et al observed no vortex formation at 40 μg mL −1 λ DNA but increasing vortex formation with higher Wi (corresponding to the Deborah number used in our work) for 400 μg mL −1 λ DNA, similar to the lack of waves for our 50 μg mL −1 sample but waves occurring at C ≥ 100 μg mL −1 .…”
Section: Discussionsupporting
confidence: 93%
“…It is known that most oil reservoirs consist of significant divalent ions such as strontium, barium, magnesium, and calcium [82][83][84] with reservoir temperature up to 120 C. 27,37 These conditions significantly reduced the applicability of injected dispersions during oil recovery due to the lack of stability caused by particle aggregation/agglomeration. Most recent research on nanotechnology-enhanced EOR focused on the effect of salinity and/or temperature without investigating the impact of surface functionalization and their influence on stability.…”
Section: Oil Recovery Analysismentioning
confidence: 99%